Dictionary of materials and testing - Tomsic, Joan L.; Hodder, Robert S. (Society of Automotive Engineers, 2000)
Advances in the fields of materials and testing have introduced hundreds of concepts and terms. This second edition of the Dictionary of Materials and Testing, emphasizes "engineered" materials that can withstand stress or unusual environments for an extended period of time.
Keywords: Materials -- Dictionaries.; Materials -- Testing -- Dictionaries.; elektronické knihy; electronic books